The phenomenology of autistic regression: subtypes and associated factors - (:unkn) unknown (SPRINGER, 2012)
This study aimed to investigate the association of autistic regression (AR) and subtypes of AR with medical, developmental and psychiatric factors. Fifty-seven children with autistic spectrum disorders (ASD) were included in the study. Two types of AR are defined as regression after a normal social/language development (type 1) and regression as the worsening of previously reported autistic features (type 2). The frequency of history of AR was 56.1%. Male gender and sleep problems were found to be associated with a positive history of AR. The frequency of gastrointestinal complaints/diseases was higher in children with regression type 2 when compared to the children with regression type 1. Future studies with larger sample size and prospective design will contribute to clarifying the phenomenology and the associated factors of AR.
Keywords: Autistic regression; Autistic spectrum disorders; Autism; Sleep problems; PERVASIVE DEVELOPMENTAL DISORDERS; ABERRANT BEHAVIOR CHECKLIST; SPECTRUM DISORDERS; LANGUAGE REGRESSION; SLEEP PROBLEMS; RATING-SCALE; CHILDREN; POPULATION; ABNORMALITIES; CHILDHOOD